The effect of sleep deprivation on choice reaction time and anaerobic power of college student athletes - Taheri, M.; Arabameri, E. (Asian Journal of Sports Medicine, 2012)
Purpose: The aim of this study was to determine the effect of one night`s sleep deprivation on anaerobic performance and Reaction time of subjects in the morning of the following day.